Coping strategies for nurses when caring for mental health care users with violent and aggressive behaviour in mental health care institutions in North West province - Van der Wath, Annatjie (University of Pretoria, 2024)
Dissertation (MNSc (Nursing Science))--University of Pretoria, 2024.